الرؤیة والرسالة لجمعیات المکتبات والمعلومات العربیة والأجنبیة: دراسة تحلیلیة مقارنة مع بیان مقترح لعینة من الجمعیات العربیة - د. نادیة عبد العزیز الصواف Abdel Aziz El Sawaf (المجلة الدولية لعلوم المكتبات والمعلومات)
Moving forward to many international events and forums in recent times isthe title of these events. The present study attempts to follow the efforts ofinternational and national professional associations and institutions in the field oflibraries and information in developing a vision for the future and developingfuture plans and strategies. International Federation of Library Associations andInstitutions in the development of IFLA global vision. The economic, technical,social, educational and political variables have influenced the future paths of alldisciplines and institutions in society, libraries, information centers, and the role ofdocuments and archives in the heart of these variables. This is the memory thatpreserves the new knowledge and is the first institution to learn about itsexistence. Affected by it.The present study aims at establishing a vision and objectives for theArab National Professional Societies through studying and analyzing the activitiesof the international associations and institutions in the field of libraries andinformation in order to achieve a vision, mission and objectives that can beapplied to Arab professional associations and institutions, the standards of thegood message and its contents, The process of preparing the message andpossible solutions, giving practical examples of the message of a number ofinternational professional associations,The study followed the analytical descriptive method to cover the websitesof Arab professional societies and associations for libraries and information onthe Internet and some sites of foreign societies. At the end of the study, anattempt was made to present a proposed model for strategic planning for thevision and objectives of the Arab national professional societies in line with thetraditions and constants and ambitions of the Arab society.